Improving utilization of rotavirus vaccination among children in Kuwait: an intervention study - Khairey, Walaa Ahmad; Labib, Nargis Albert; Alenzi, Ali Noufal Yaloos Alkhalaf; Abdullah, Fahad Hamed Medhi; Abdelmoaty, Alshaimaa Mohamed (International Journal of Public Health Science (IJPHS), 2023)
Vaccination against rotavirus is an effective strategy to overcome the consequences of rotavirus infection. This study aims to raise the knowledge, attitude, and practice (KAP) of both parents or caregivers and healthcare providers towards the rotavirus vaccination. The design of the study was an interventional pre-test and post-test. The type of intervention used in this study is an educational intervention. The intervention consisted of a health education message delivered to the participants including both parents or caregivers and healthcare providers. It included three phases, the first one was carried out to assess the KAP of mothers and caregivers before the intervention, the second phase involved the evaluation of participants’ post-intervention, and the third phase involved the assessment of healthcare providers. The study used a survey to assess the demographics, KAP of the participants. The collected data was analyzed using the SPSS program. The overall KAP among mothers were high (11.6%). After the intervention, the level of KAP of mothers toward the rotavirus vaccine was improved significantly (p=0.0001). Also, after the health education message, the level of KAP of the healthcare providers was significantly improved (p=0.0001). The levels of KAP of mothers and healthcare providers were improved after the educational intervention and the health educational message, reflecting the important role of educational intervention in raising the awareness of both mothers and healthcare providers.